FOSTERING INNOVATION IN PUBLIC SERVICE THROUGH TRANSFORMATIONAL LEADERSHIP IN TAX OFFICES: THE CASE IN EAST JAVA REGIONAL TAX OFFICE THREE - Bakti, Dhani Waluyo; Meutia, Meutia; Maharani, Anita (DIA: Jurnal Administrasi Publik, 2025)
This research aims to explore factors that can influence innovative work culture and knowledge-sharing culture in public services, and this is interesting to study, considering that the direction from the Ministry of Finance is that institutions under this ministry must be able to have a spirit of innovation. The literature adopted in this research includes literature related to the variables studied. This research approach refers to a quantitative approach involving 198 respondents, with analysis techniques referring to the Partial Least Square Structural Equation Modelling approach. The results obtained showed that two of the four hypotheses were not supported. The results of this research reflect an opportunity to explore further the factors that can encourage the realization of innovative work behavior and knowledge-sharing culture among employees who have worked for more than ten years, men and aged between 31-40.